Effect of internship performance and work motivation on vocational students’ work readiness - Rochmayanti, Failla; Kuat, Tri; Tentama, Fatwa (International Journal on Education Insight, 2022)
The purpose of this study was to determine the effect of internship performance and work motivation on work readiness of students in SMK Negeri 1 Bantul Yogyakarta, majoring in automation and office governance competencies in academic year 2018/2019. This research is an ex post facto using quantitative correlation method. The population of this research is all XII grade students of in office automation and governance expertise, with a total of 64 students. We selected 30 students as the sample using proportionate random sampling technique. The dependent variable in this study is work readiness (Y) while the independent variables include the performance of internship (X1) and work motivation (X2). Data collection methods are questionnaires and documentation. The method of data analysis uses descriptive statistics, and multiple linear regression. The results showed that there was an influence on the performance of internship and work motivation both individually and simultaneously on the work readiness of students of SMK Negeri 1 Bantul.